Factors associated with tobacco consumption in university students of Lima metropolitan - Correa-López, Lucy E. (2020)
Introduction: The consumption of tobacco is very harmful to people’s health. According to WHO, smoking is the cause of death of 8 million people a year. Objetive: The purpose of the research was to determine the factors associated with the consumption of tobacco in university students in Metropolitan Lima. Methods: The sample consisted of 447 students from Lima universities, the survey was applied: Fagerstrom test. Subsequently the data was analyzed using tables of: distribution, frequency, contingency.  Results: It was evidenced through the X2 statistical test that there is a significant association between the variables sex and smoking habit, OR = 1.93, IC 95%[1.29-6,519]. It was also observed that having smoking parents is significantly associated with the habit of smoking by the children, with a value p =0,000 of X2 and the OR 3.31, IC 95%[2,145 - 5,116]. Conclusion: The variables sex and parental background have a significant association with tobacco consumption, emphasizing that our family environment deserves to be safe, healthy and free of tobacco smoke